The influence of attitude on e-services Majlis Perbandaran Sungai Petani, Kedah / Amni Syaza Zakaria and Siti Nur A'qilah Wazi - Zakaria, Amni Syaza; Wazi, Siti Nur A'qilah (2018)
E-services have become the one of technology advancement that very vital in the entire world. It is because government already established this under Malaysian flagships of e-Government and need to be implemented in every sector in delivering their services. The study examines the influence of attitude on eservices at Majlis Perbandaran Sungai Petani Kedah (MPSPK). A cross sectional survey among public in Merbok area was applied and used in this study. The numbers of questionnaire distributed were 74 completed questionnaires and all had been answered and returnable. The data obtained were analysed and these following findings were found out. The relationships of perceived usefulness, perceived ease of use and compatibility were further examined. All of these relationships were found to be significant. However, the extent of attitude among the public in Merbok area were still at the moderate level since the issues there are not all the user accept to use this e-services. The study also provides strong evidence that it is essential to raise the attitude to increase numbers of e-services usage.